Advances in Anti-inflammatory Activity, Mechanism and Therapeutic Application of Ursolic Acid - Luan, Mingzhu; Wang, Huiyun; Wang, Jiazhen; Zhang, Xiaofan; Zhao, Fenglan; Liu, Zongliang; Meng, Qingguo (Mini Reviews in Medicinal Chemistry, 2022)
In vivo and in vitro studies reveal that Ursolic Acid (UA) is able to counteract endogenous and exogenous inflammatory stimuli and has favorable anti-inflammatory effects. The antiinflammatory mechanisms mainly include decreasing the release of histamine in mast cells, suppressing the activities of lipoxygenase, cyclooxygenase and phospholipase, and reducing the production of nitric oxide and reactive oxygen species, blocking the activation of the signal pathway, downregulating the expression of inflammatory factors, and inhibiting the activities of elastase and complement. These mechanisms can open up new avenues for the scientific community to develop or improve novel therapeutic approaches to tackle inflammatory diseases, such as arthritis, atherosclerosis, neuroinflammation, liver diseases, kidney diseases, diabetes, dermatitis, bowel diseases, cancer. The anti-inflammatory activity, the anti-inflammatory mechanism of ursolic acid and its therapeutic applications are reviewed in this paper.
Keywords: inhibitory activity